Processing Trauma: A Case Study - Hamilton, Jenny (2013)
This dissertation is informed by a bio psychosocial model of trauma, synthesising elements of emotional processing, information processing, social cognitive, biochemical, evolutionary and psychosocial perspectives. It is an adaptive model of individuals striving to make sense of, narrate and come to terms with difficult events, as part of the organisms’ tendency towards growth. However, Person Centred theory has so far accounted for trauma through a defence model (Joseph, 2004). Warner (2005, 2009) reconsiders Roger’s theory of personality, and argues that its defence premise presents a distortion of person centred theory. She instead develops a process – oriented account of personality development, trauma and psychological distress that accounts for the social construction of meaning as part of the interplay between individual processing and wider culture.